Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di SDN Tambaksari I - Dwi Oktavia; Syunu Trihantoyo; Windasari Windasari (Journal on Education, 2023)
This research has a goal to find out: (1) the planning of school operational funds at SDN Tambaksari I; (2) the management of school operational funds at SDN Tambaksari I; and (3) the transparency and accountability for school operational funds at SDN Tambaksari I. Qualitative descriptive was used as a research method in this study with data collection in the form of observation, interviews, and documentation with the school principal and related staff. The results of the study show that schools can plan and manage school operational assistance funds (BOS) in accordance with Permendikbudristek No. 63 of 2022. Schools also use the ARKAS and SIPlah applications according to guidelines for regulating planning, management, and reporting to increase credibility, transparency, and school accountability.